Effects of polybrominated biphenyls on kidney function and activity of renal microsomal enzymes. - McCormack, K M (1978)
Polybrominated biphenyls (PBBs) cause hepatic microsomal enzyme stimulation and histopathological alterations in several organs, including kidney. Concern about effects of PBBs on the health of newborns has increased after the discovery of PBBs in milk of nursing mothers. Therefore, it was of interest to investigate the effects of PBBs on kidney function and the activity of renal microsomal enzymes in adult and immature animals. Seven and eleven day old pups were treated with a single IP injection of either peanut oil or 150 mg/kg PBBs (FireMaster BP-6) in peanut oil. Adult virgin rats were fed diet containing 0 or 100 ppm PBBs for 30 or 90 days. Treatment with PBBs only retarded weight gain after 90 days exposure. Kidney-to-body weight ratio was not altered by PBBs. Arylhydrocarbon hydroxylase activity was increased while epoxide hydratase activity was decreased (adults) or not affected (immature rats) in kidney following treatment with PBBs. Administration of PBBs had no effect on blood urea nitrogen, the clearance of inulin, p-aminohippurate (PAH), or fractional sodium excretion. Similarly, the in vitro accumulation of PAH and N-methylnicotinamide (NMN) by thin renal cortical slices and ammoniagenesis and gluconeogenesis in renal cortical slices were not affected by PBBs. In conclusion, treatment with PBBs resulted in modification of the activity of renal microsomal enzyme activities but had no detectable effect on renal function.